Evaluation of husband–wife communication regarding family planning among the couple of reproductive age group in the field practice area of Prathima Institute of Medical Sciences, Karimnagar - Gayathry, Dasari; Ramsagar Reddy, M.; Rammana, B. V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Fertility decisions occur within specific social contexts and social norms therefore restrict individual decisions on fertility and behaviors related to family planning such as spacing and limiting of births and using contraception which reflects the importance of effect of inter-spousal communication on the contraceptive method choice and future intention of method use. Hence the objective of present study is to evaluate the husband wife communication and contraceptive use, method choice and timing of initiation of discussion among couples in study area. Methods: A cross - sectional study was conducted during February 2013 - January 2014 among couples residing in the field practice study areas. A semi-structured questionnaire consisting of socio-demographic characteristics, questions related to awareness, sources and decision making towards family planning was administered to 406 couples of study area. Results: It has been observed that regarding decision making, about 39.4% of the men had taken a decision on the use of contraceptive methods, and only 21.7% wives had autonomy of using contraception of their choice. Around 67.5% of the men had discussion with their wives about the family planning and more than half (57%) of the time the discussion was initiated by men. Conclusions: Husband was the decision maker in nearly half of the couples and family planning was discussed among majority of respondents. Family planning education should be encouraged through effective IEC programs and strategies for promoting husband wife communication should be considered inorder to increase family planning adoption.